(untitled) (AYUSHDHARA, 2023)
Sidhhamantra Nighantu is one such unique lexicon which has a chapter named as Tridoshaghna Varga which enlists the drugs which pacify one, two or all the three Doshas i.e., Vata, Pitta and Kapha. Drugs pacifying all the three Doshas are unique in their Rasa Panchaka in terms of specific combination of Rasa, Guna, Virya and Vipaka. The Tridoshaghna concept and this chapter both stand unique and hence the present chapter was selected for its exploration through multiple correspondence analysis. Materials and Methods: All the relevant information about the drugs like their Botanical identity, family, Rasa, Guna, Virya and Vipaka of Tridoshaghna varga was collected with the help of previous and successive texts of Sidhhamantra Nighantu. The collected information was subjected to multiple correspondence analysis. Result: The chapter Tridoshaghna Varga enlists several substances of herbal origin, metallic/mineral origin and animal origin. MCA revealed that the combination of Sheeta Virya and Madhura Vipaka with the combination of Tikta and/or Katu Rasa can be the best properties for Tridoshaghna action in majority diseased conditions. Conclusion: The study data should be considered while clinical practice by clinicians and further studies should be carried out on the nutritional foods included in the chapter for better understanding of Aahara (nutritional herbs) as well as Aushadha (medicinal herbs) for Tridoshaghna action.